Model Struktural Faktor-Faktor Berpengaruh Terhadap Kinerja Badan Usaha Milik Desa di Kabupaten Jembrana, Bali - Gandhiadi, G K; Eka N Kencana, I Putu (Jurnal Matematika; Vol 10 No 1 (2020)DO - 10.24843/JMAT.2020.v10.i01.p118, 2020)
One of the efforts to develop the rural economy is the establishment of economic institutions such as Village-Owned Enterprises (BUMDes) which are supported by the role of the local government and are based on the wishes of the village community. This BUMDes is expected to be able to increase market demand based on proper management of the existing village potential. Through cooperative behavior (social capital), synergy and a good entrepreneurial orientation in BUMDes managers and the positive role of the government it is hoped that there will be an increase in BUMDes business performance in Jembrana Regency. The purpose of this study is to comprehensively analyze the role of government and social capital of business managers through entrepreneurial orientation towards BUMDes business performance in Jembrana Regency. The basis of multivariate analysis used is Structural Equation Modeling (SEM). Through a research sample of 90 respondents from BUMDes managers in Jembrana Regency, the results are obtained: (1) social capital and the role of government directly have a positive but not significant effect on business performance, while entrepreneurial orientation has a positive and significant effect on business performance, and (2) social capital and the role of the government in a total positive and significant effect and require full mediation (full mediation) through entrepreneurial orientation to the business performance of BUMDes in Jembrana Regency, Bali.